Idealen en werkelijkheid in de Russische literatuur - Kropotkin, Peter; Mac LeoMaertens, Fanny (Gent Amsterdam : Ad. Herckenrath S.L. Van Looy, 1907)
Collectie 'Vrijzinnige Werkmansbibliotheek'
Nederlands
Monografie